Life history and host range of the mango pulp weevil, Sternochetus frigidus (Fabr.) in Palawan, Philippines - De Jesus, Louella Rowena A.; Gabo, Richard R. (2000)
The life history of the mango pulp weevil, Sternochetus frigidus (Fabr.), was studied in Puerto Princesa City, Palawan, the only area in the Philippines where the pest has been reported. Total development of S. frigidus in 'Carabao' mango from egg to adult stage is 32 days with five larval instars. The female lays eggs singly on the fruit peel and covers it with secretions, which hold the eggs in place. The five larval instars develop inside the fruit. The adult remains in its pupal cell inside the fruit until the latter is fully rotten, in an average of 37 days. Seventy percent (70%) of the adult weevils are able to exit from the fruit by boring a hole directly opposite the pupal cell. The rest are trapped inside the dried and rotten fruit, which leads to death. The weevil infested 'Mampalang', 'Carabao', 'Wani', 'Katchamita', 'Pico', and 'Apple' mango in Palawan. It did not infest other fruit crops.
Keywords: Mango -- Diseases and pests; Mango weevil; Fruit diseases and pests